Parental Communication Patterns Towards Children with Special Needs During Puberty in Malalayang District, Manado City - Harilama, Stefi Helistina (Journal of Management and Administration Provision, 2024)
Children are a gift that must be guarded, cared for and educated. Children who are born in a healthy or normal condition are the pride of parents. However, in reality there are still parents who have children who experience obstacles, disorders and delays in mental and physical growth called Children with Special Needs. The challenge is when children start to enter puberty, children will enter adolescence at this age, of course it will affect their physical and mental, for example, girls are marked by menstruation or menstruation. Conditions like this affect not only children but also parents. Because automatically parents must go directly to help. Unlike boys, physical changes do not have a big impact. Based on the characteristics of psychological growth, ABK is actually almost the same as normal children, for example, emotionally, the instinct to sympathize with others or the opposite sex is there. It's just that self-control is limited. For that, children with special needs in adolescence must continue to receive supervision from parents who must be more intensive in accompanying and even controlling children's actions. Based on the above phenomenon, the researcher is interested in conducting further research and this study is entitled Interpersonal Communication Patterns of Parents and Children with Special Needs During Puberty in Malalayang District. The aim is to find out how the communication patterns of parents who have children with special needs with the type of intellectual disability. Using the theory of Interpersonal Communication from Joseph Devito using qualitative methods and purposive sampling techniques where the informants needed in this study are parents who have adolescent children with special needs in Malalayang District, Manado City.